Microstructure Development during Crystallization of Tin and Tin-Based Alloys under High-Gravitational Fields Simulated by Centrifugal Acceleration - Leung, Jackie (My University, 2009)
Succinonitrile, commercially-pure Sn, Sn-0.3 wt% Cu, and Bi-Sn of several weight ratios were solidified under high-gravitational fields 287 times that of the earth's gravity simulated by centrifugal acceleration. The microstructure of the samples solidified in high-gravity was examined and compared with those solidified in normal gravity. Solidification was also done under varying cooling rates to determine its combined effect with high-gravity on microstructure development. The microstructure was quantified in terms of grain size, eutectic spacing, and primary phase distribution against the radial position of the samples. Vickers hardness of the samples was also measured by using both low load and a high load, in order to determine the solidified samples' relative strength.
The microstructure of the Sn sample solidified in high-gravity possessed a higher percentage of small grains than that solidified in normal gravity. For Bi-Sn alloys solidified by slow-cooling, the eutectic phase formed in high-gravity had a complex but regular lamellar structure whereas that formed in normal gravity was irregular. In the hyper- and hypoeutectic Bi-Sn sample, the primary phase was segregated to the inner or outer radius of the samples formed in high-gravity, depending on the variation of density between the phases. The Sn-Cu alloy solidified in high-gravity had a cellular structure whereas that solidified in normal gravity had a dendritic structure.
The effects of high-gravity on microstructure development are explained by the enhanced fluid flow and Rayleigh-Bénard convection during solidification of the melt. This convection is caused by thermally-induced density gradients within the melt and is confirmed by calculating the Rayleigh number. Other effects on microstructure are explained in terms of the Stokes equation and the Mullins-Sekerka criteria for solidification stability. Change in the solidification temperature as a result of increasing centrifugal acceleration was calculated from the Clausius-Clapeyron equation, and its magnitude is discussed.
Keywords: Materials Science and Engineering; Materials Science and Engineering